Prevalence of Hypertension in Rural South Gujarat and Risk Factors Associated With It - Aman Damor; Shreyash Mehta (Medsci Publications, 2021)
Introduction: Hypertension is one among the main health and development challenges of the 21st century. Prevalence of Hypertension varies in every community. To tackle this important health problem, we need to understand it's prevalence and important factors associated with it. This study was carried out to find out the prevalence of Hypertension in study subjects also to find the risk factors correlated with Hypertension. Materials and Methods: A Cross-sectional study was administered among 738 individuals of 30 years and above attending Out Patient Department (OPD) in three Primary Health Centre of South Gujarat during June 2019-March 2020. A pretested predesigned questionnaire was used to collect demographic data by interview technique. Results: Among 738 patients, the prevalence of hypertension was 41.7%; out of this, 28.7% were conscious of their hypertensive status while 13% were newly diagnosed cases. The association between hypertension with increase in age, family history of hypertension, increase salt intake, consuming mixed diet, increase waist circumference, waist hip ratio and body mass index were found significant. Physical inactivity, gender, tobacco and alcohol consumption were not significantly associated with hypertension. Conclusions: The prevalence of hypertension in country is comparatively high. Extensive efforts are required for raising the notice level & regular screening of high-risk population is suggested for preventing the complications & disability.